Factors Associated With Depressive Symptoms in Individuals Who Have Experienced COVID-19 Self-Quarantine - Hye-Young Jang; Young Ko; Song-Yi Han (Frontiers Media S.A., 2022)
The purpose of this study was to identify the factors associated with depressive symptoms in individuals who have experienced self-quarantine because of coronavirus disease exposure or infection using Lazarus and Folkman's stress, coping, and adaptation theory, and George's Social Antecedent Model of Depression. This was a cross-sectional study that used data from the 2020 Korean Community Health Survey. A complex sample design was used to analyze the data. Descriptive statistics, the Rao-Scott X2 test, and logistic regression analysis were conducted to identify factors associated with depressive symptoms. Approximately 5.3% of the subjects had depressive symptoms. The factors associated with depressive symptoms were age, level of education, household income, changes in daily life due to coronavirus disease, whether someone provided assistance during the self-quarantine, perceived health status, and hospital consultation due to depressive symptoms. The findings of this study will be utilized as basic data for the development of programs to alleviate and prevent depressive symptoms in self-quarantine individuals.